Oral health associated with incident diabetes but not other chronic diseases: A register-based cohort study - Heikkilä, Pia; Niskanen, Leo; But, Anna; Sorsa, Timo; Haukka, Jari (Frontiers in Oral Health, 2022)
Introduction: Oral infectious diseases are common chronic oral diseases characterised by a chronic inflammatory condition. We investigated chronic oral diseases as potential risk factors for systemic chronic diseases, diabetes mellitus, connective tissue diseases, seropositive rheumatoid arthritis, ulcerative colitis and Crohn disease, as well as severe psychotic and other severe mental disorders. Methods: The cohort comprised 68 273 patients aged ≥ 29 years with at least one dental visit to Helsinki City Health Services between 2001 and 2002. The cohort was linked to the data on death (Statistics Finland), cancer (Finnish Cancer Registry), and drug reimbursement (Finnish Social Insurance Institution) and followed until death or the end of 2013. The outcomes of interest were the incidences of chronic diseases measured starting of special refund medication, which means Social Insurance Institution partly or fully reimburses medication costs. Outcomes of interest were: diabetes mellitus, connective tissue diseases, seropositive rheumatoid arthritis, ulcerative colitis and Crohn´s disease, and severe mental disorders. Results: The mean follow-up time was 9.8 years. About 25% of the study population had periodontitis, 17% caries, over 70% apical periodontitis, and 9% < 24 teeth at the start of follow-up. Diabetes was the only chronic systemic condition associated with oral health variables. Having 24-27 teeth was associated with a higher incidence rate ratio (IRR) (1.21, 95% confidence interval 1.09-1.33) compared to having 28 or more teeth; the IRR for having 23 or less was 1.40 (1.22-1.60). Having periodontitis (1.10, 1.01-1.20), caries (1.12, 1.01- 1.23), or apical periodontitis (1.16, 1.04-1.30) is also associated with a higher risk of diabetes. Conclusion: Our epidemiological 10 years follow-up study strongly suggests that the association exists between chronic oral diseases and diabetes, warranting close collaboration among patient´s health care professionals.